Mengelola Limbah Plastik Menjadi Bahan Kerajinan di SDN Batu Ampar 1 - Melany Novarelia Putri; Muhammad Robith Hasymi Ash Shidqi; Lutfi Abdullah Yazid; Dina Maisa Putri; Muhamad Ramadhani Septa Hariansyah; Hasbi Mubarak Suud; Dwi Erwin Kusbianto; Agung Nugroho Puspito (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This community service activity was designed to increase elementary school students' understanding and creativity regarding plastic waste management through handicraft making. This activity was carried out at SDN Batu Ampar 1 Cermee, Bondowoso Regency, involving 49 students from grades IV to VI. The implementation method consisted of four sessions, namely the delivery of information about plastic waste, understanding organic and inorganic waste, practicing making collages from plastic waste, and evaluation through pre-tests and post-tests. The evaluation results showed an increase in the average score of student understanding from 56.3 to 82.1, which means an increase of 25.8 points after the activity was carried out. In addition, the students successfully created several collage works from plastic waste that reflected their growing creativity and concern for the environment. This activity proved to be successful in increasing environmental awareness and recycling skills from an early age and has the potential to be implemented in other elementary schools.